Rapidly fatal respiratory failure and angioimmunoblastic lymphadenopathy: possible contributions of immunoblastic leukaemia, chemotherapy, and multiple antibodies directed against mature blood cells. Issue 5 (May 1981) - Trenchard, P M; Whittaker, J A; Gough, J; Parry, H
Abstract : A patient with angioimmunoblastic lymphadenopathy, immunoblastic leukaemia, pulmonary immunoblastic infiltration, and multiple antihaemocytic antibodies in his serum deteriorated rapidly after chemotherapy due to severe progressive respiratory of dysfunction. The haematological and immunological changes that accompanied this are described and discussed in the light of the pulmonary changes observed at necropsy of pulmonary oedema, fibrinous thrombi within venules, and immunoblastic infiltration of these thrombi and the venule walls. A pathophysiological mechanism is postulated in an attempt to rationalise these findings, and to act as a guide for the future assessment and management of similar cases.